Managing cognitive load with a flipped language class: An ethnographic study of the student experience. (21st August 2019) - Tonkin, Kati; Page, Sara; Forsey, Martin
Abstract: This ethnographic study of a beginning‐level German course at an Australian university examined the student experience of learning second language (L2) grammar in a flipped classroom. Students accessed explicit grammar instruction and completed grammar exercises prior to attending face‐to‐face classes; during class, the structures were briefly reviewed by the students and then applied in interactive task‐based activities focused on meaningful use of the L2. In surveys and interviews, learners reported that the opportunity to manage the pace and depth of their interaction with online grammar modules facilitated their learning and increased their confidence. Linking these outcomes to research that has shown that flipped teaching models reduce or assist in the management of cognitive load, the study presents a compelling case for flipping the L2 classroom. The Challenge: Although most second language classes emphasize interactive activities, the common practice of delivering explicit grammar instruction in class effectively incorporates instructor‐centered "mini‐lectures" into this space. If grammatical structures are presented in videos accessed online prior to class, what happens? To what extent can flipping instruction ease cognitive load and increase students' confidence using the language?